Diversity of class 1 integron gene cassette Pc promoter variants in clinical Escherichia coli strains and description of a new P2 promoter variant - Vinué, Laura; Jové, Thomas; Torres, Carmen; Ploy, Marie-Cécile (International journal of antimicrobial agents, 2011)
Gene cassettes of class 1 integrons may be differently expressed depending on the Pc promoter variant as well as occasionally from a second promoter located downstream of Pc, named P2. So far, the distribution of the variants has only been described in an in silico study. In this study, the prevalence of these variants in vivo was analysed in a population of 85 Escherichia coli strains from a variety of phylogenetic groups isolated from healthy subjects and clinical samples in Spain and France from 2004 to 2007. The weakest variants (PcW and PcH1) prevailed (variants associated with the integrase having the most efficient excision activity), whilst the two strongest variants, PcW TGN-10 and PcS, were less frequent. Furthermore, a new variant of P2 associated with PcW was characterised in one integron (harbouring the gene cassette bla OXA-1– aadA1) from a French strain of a healthy subject. This variant was hereafter named P2m3 and shows a G → A substitution in its −10 element (TACA GT to TACA AT), a mutation that doubled the strength of P2 and approached the level of expression of the strong PcW TGN-10 variant. When the correlation between the Pc variants and the origin of the strains was analysed, no significant difference ( P < 0.05) was observed in the Pc variant distribution according to the geographic origin or clinical setting.